Endometrial Cancer Immune Escape Mechanisms: Let Us Learn From the Fetal–Maternal Interface - Valentina Bruno; Giacomo Corrado; Denisa Baci; Benito Chiofalo; Maria Antonia Carosi; Livia Ronchetti; Emilio Piccione; Adriana Albini; Adriana Albini; Douglas M. Noonan; Douglas M. Noonan; Giulia Piaggio; et al. (Frontiers in Oncology, 2020)
The immune escape mechanisms at the base of tumor progression in endometrial cancer mimic immune tolerance mechanisms occurring at the maternal–fetal interface. The biological and immunological processes behind the maternal–fetal interface are finely tuned in time and space during embryo implantation and subsequent pregnancy stages; conversely, those behind cancer progression are often aberrant. The environment composition at the maternal–fetal interface parallels the pro-tumor microenvironment identified in many cancers, pointing to the possibility for the use of the maternal–fetal interface as a model to depict immune therapeutic targets in cancer. The framework of cancer environment signatures involved in immune adaptations, precisely timed in cancer progression, could reveal a specific “immune clock” in endometrial cancer, which might guide clinicians in patient risk class assessment, diagnostic workup, management, surgical and therapeutic approach, and surveillance strategies. Here, we review studies approaching this hypothesis, focusing on what is known so far about oncofetal similarities in immunity with the idea to individualize personalized immunotherapy targets, through the downregulation of the immune escape stage or the reactivation of the pro-inflammatory processes suppressed by the tumor.